Preliminary analysis of ophthalmic prednisolone acetate and diclofenac on diabetes mellitus regulation in 12 of 40 dogs - Stuckey, Jane Ashley (Kansas State University, 2014)
Objective- To evaluate the use of a topical ophthalmic steroid (1% prednisolone acetate) and non-steroidal anti-inflammatory drug (0.1% diclofenac) on blood glucose concentrations, serum fructosamine concentrations, and clinical scores in diabetic dogs with cataracts using descriptive analysis. Animals- Twelve client-owned dogs with naturally-occurring, controlled (per history and physical examination), insulin-treated diabetes mellitus and cataract. A total of 40 dogs will be enrolled in the study, as determined by power analysis. Procedures- This was a prospective, randomized, double-masked, experimental study with 2 phases of data collection. Dogs were enrolled from October 2011 to March 2014 and were assigned to 1 of 2 treatments (Drug Red or Drug Blue) using blocked randomization; dogs received either 1% prednisolone acetate suspension or 0.1% diclofenac solution. Patient history, physical, and ophthalmic examinations were performed and a clinical score assigned at enrollment (Phase 1 [day 0]) and upon return (Phase 2 [day 32]). At these times, a complete blood count, serum chemistry, urinalysis, and serum fructosamine concentration were performed prior to hospitalization for up to 72 hours for continuous glucose monitoring. For 4 weeks (day 3 to 31), dogs returned home, and owners administered the dispensed ophthalmic medication 4 times daily to both eyes. Descriptive analysis of data was performed; statistical analysis will follow enrollment of 40 dogs. Results- Twelve dogs have completed the study, with 6 dogs assigned to each treatment group. Dogs received 4.44 or 0.44 mg/day of prednisolone acetate or diclofenac, respectively. Dogs assigned to Drug Red more commonly exhibited elevations in serum liver enzyme activity. Drug Red group showed a greater percent increase in fructosamine concentrations over time. Based on glucose curves alone (22 curves analyzed), an insulin dose increase was recommended for 12 curves. An insulin dose decrease and no dose change were recommended for 5 curves each. During treatment, 1 dog reportedly developed polyuria and polydipsia. Conclusions- Descriptive analysis revealed differences in some outcomes of interest among dogs treated with 2 different ophthalmic anti-inflammatory medications. Data collection is ongoing to determine if statistically significant differences exists for outcomes per group.
Keywords: Diabetes mellitus; Dog; Cataract; Lens-induced uveitis; Phacolytic uveitis; Ophthalmic; Veterinary Medicine (0778)